2019
DOI: 10.2215/cjn.14631218
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis–Associated Peritonitis

Abstract: Peritonitis is a common and severe complication in peritoneal dialysis (PD). Detailed recommendations on the prevention and treatment of PD-associated peritonitis have been published by the International Society for Peritoneal Dialysis (ISPD), but there is a substantial variation in clinical practice among dialysis units. Prophylactic antibiotics administered before PD catheter insertion, colonoscopy, or invasive gynecologic procedures, daily topical application of antibiotic cream or ointment to the catheter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 49 publications
2
69
0
2
Order By: Relevance
“…PD-related infections including peritonitis and exit-site/tunnel infections remain major complication that can lead to technical failure or even death [ 22 ]. There are many studies suggesting that the prevention of peritonitis is necessary for the improvement of catheter survival as well as the long-term success of peritoneal dialysis [ 23 ]. Overall, we observed less episodes/patients-year of peritonitis and exit-site infection in the “Half-Perc” group during 365 days follow-up time, but both complications were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…PD-related infections including peritonitis and exit-site/tunnel infections remain major complication that can lead to technical failure or even death [ 22 ]. There are many studies suggesting that the prevention of peritonitis is necessary for the improvement of catheter survival as well as the long-term success of peritoneal dialysis [ 23 ]. Overall, we observed less episodes/patients-year of peritonitis and exit-site infection in the “Half-Perc” group during 365 days follow-up time, but both complications were not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms could explain the negative effect of hyperuricemia on RD in PD patients. First, it has been demonstrated that the number of peritonitis episodes are associated with RRF reduction [5,19,23]. Considering the fact that peritoneal clearance dominates in SUA balance and peritonitis is a significant risk factor for structural and functional alterations in the peritoneal membrane in PD patients, an increased risk of RD decline might be observed in patients with hyperuricemia [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been demonstrated that the number of peritonitis episodes are associated with RRF reduction [5,19,23]. Considering the fact that peritoneal clearance dominates in SUA balance and peritonitis is a significant risk factor for structural and functional alterations in the peritoneal membrane in PD patients, an increased risk of RD decline might be observed in patients with hyperuricemia [23,24]. Second, it has been postulated that a high SUA level induces systemic and intraperitoneal inflammation [15,18,25].…”
Section: Discussionmentioning
confidence: 99%
“…Peritonitis, an infection within the peritoneal cavity mainly caused by bacteria, is the most frequent complication of PD [ 160 ]. Measures to limit infection risk and to ensure prompt and appropriate investigation and treatment have lowered peritonitis rates and improved outcomes, but peritonitis remains a major determining factor in mortality and in adverse outcomes, including peritoneal inflammation and membrane failure [ 161 ]. The immune response to infectious peritonitis is initially characterized by neutrophil recruitment, with subsequent transition to monocyte predominance [ 162 ].…”
Section: Peritoneal Impact Of Il-17amentioning
confidence: 99%